2010
DOI: 10.2190/ec.43.1.e
|View full text |Cite
|
Sign up to set email alerts
|

Peer Feedback in a Large Undergraduate Blended Course: Perceptions of Value and Learning

Abstract: This study examined students' perceptions of peer feedback and learning in a large, undergraduate course that incorporated supplementary online discussions. Peer feedback (PF) was facilitated via an automated rating system, within Blackboard discussion forums, for half of the students enrolled in the course. Following the peer feedback process, students in the PF group perceived higher levels of confidence and comfort for posting and responding in online discussions than students who did not receive peer feedb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 19 publications
6
14
0
Order By: Relevance
“…The results suggest that students perceived the online learning more interesting and more autonomous and perceived themselves more efficacious to perform the learning tasks when the quality of their work was well recognised by their peers. These findings are consistent with previous studies suggesting that peer feedback is an effective instructional strategy that promotes students’ engagement in learning activities (Reese‐Durham, 2005; Topping, 1998), increases students’ perceived competence (Chacko et al , 2006; Ertmer et al , 2010) and supports building cohesiveness among online learners (Gaytan & McEwen, 2007).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results suggest that students perceived the online learning more interesting and more autonomous and perceived themselves more efficacious to perform the learning tasks when the quality of their work was well recognised by their peers. These findings are consistent with previous studies suggesting that peer feedback is an effective instructional strategy that promotes students’ engagement in learning activities (Reese‐Durham, 2005; Topping, 1998), increases students’ perceived competence (Chacko et al , 2006; Ertmer et al , 2010) and supports building cohesiveness among online learners (Gaytan & McEwen, 2007).…”
Section: Discussionsupporting
confidence: 92%
“…Chacko, Seetharaman and Murthy (2006) found that the use of peer feedback supported medical interns’ perceived competence to progressively increase. Ertmer et al (2010) also found that peer feedback helped students perceive higher levels of confidence and comfort for posting and responding in online discussions.…”
Section: Influence Of Motivation and Peer Feedback On Discussion Behamentioning
confidence: 96%
“…In addition, some research indicates a 'knock on' effect to other areas of learning, for example, Dengler (2008) found that once students have contributed to an online discussion, they are more likely to participate in face to face discussions. Although it is arguable that blended learning may offer a more neutral environment where students are able to participate equally, evidence regarding the impact of social and cultural factors on VLEs so far is inconclusive (Ertmer, Richardson et al 2010;McNulty et al 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In line with the findings of Bertera and Littlefield (2003), some students alluded to the sense of community online forums created, for example, 'great, loved reading others' and 'good to see additional points of view'. One student commented verbally, that she had never felt so well supported within a group, which may have resulted from a possible 'knock on' effect of using online forums (Ertmer, Richardson et al 2010). Finally, students commented on how online forums enhanced higher learning skills, such as, shared learning and critical thinking, for example, 'thought provoking comments offered another perspective I may not have thought of.'…”
Section: Tablementioning
confidence: 99%
“…Many claims have been made about the benefits of peer learning and there is now substantial evidence to suggest students can make useful contributions to each other's learning (Ertmer et al 2010;Hammond 2005;Riese, Samara, and Lillejord 2012;Stone, Cooper, and Cant 2013;Topping 2005).…”
Section: Peer Learningmentioning
confidence: 99%